Legal Protection For Consumers in Online Buying and Sellin Transactions in Indonesia Reviewed From Law Number 8 Of 1999 Concerning Consumer Protection - Glaidy Angelina Nayoan; Nur Mohamad Kasim; Zamroni Abdussamad (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Due to the quick advancement of digital technology, online purchasing and selling has become easier. Online transactions do, however, come with a number of drawbacks, including fraud, mismatches between products and their descriptions, and privacy violations. With reference to Law Number 8 of 1999 on Consumer Protection, the purpose of this study is to examine the legal safeguards that Indonesian consumers have when making purchases online. The study's results, which were obtained using a normative juridical research methodology with an emphasis on statutory regulatory analysis, indicate that while the Consumer Protection Law creates a basic legal framework, more oversight and regulations are necessary to ensure its greater efficacy when applied in the digital sphere.